Patterns of scholarship in scholarly journal publication in SA: the case of Perspectives in Education (PIE) - Cross, Michael (South African Journal of Higher Education, 2016)
The paper explores the role of PIE in the production, legitimation and distribution of educational scholarship in SA. It is an exploratory analysis in two senses, theoretically and methodologically. Theoretically, it examines the field of scholarly publication as represented in current scholarly journals. Methodologically, it represents the first systematic attempt to develop and test an analytical framework for understanding patterns and trends in journal publication in SA. It deals broadly with three main analytical areas: (i) the biography of the journal, its origins and evolution, with particular attention to the shifts in policy and governance; (ii) the authors, their origin, gender, race, institutional affiliation and academic credentials; and (iii) the objects of study and their disciplinary basis. The argument articulated posits two main claims. First, despite the restructuring of the editorial board and earlier capacity building efforts, the race and gender imbalances persist with an almost white monopoly over authorship. Second, PIE has found it difficult to break away from the insularity inherited from apartheid, a challenge that requires greater aggressiveness in attracting cutting edge international work.